2006
DOI: 10.1590/s0100-67622006000400011
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de produção de óleo-resina de copaíba (Copaifera spp) de populações naturais do sudoeste da Amazônia

Abstract: O potencial de produção de óleo-resina extraído de Copaífera spp foi avaliado em duas populações naturais do sudoeste da Amazônia brasileira (municípios de Tarauacá e Xapuri), nos anos de 2000 e 2001. Foram selecionadas 388 árvores adultas de copaíbas das duas populações, sendo identificados em cada árvore o diâmetro à altura do peito (DAP), a produção de óleo-resina, a posição da árvore no relevo local (baixio ou terra firme) e a tipologia florestal local (floresta aberta ou densa), além do nome regional da c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
3
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 5 publications
4
28
3
15
Order By: Relevance
“…The shape of the diameter distribution of regeneration was not negative exponential (i.e., inverted J). Negative exponential diameter and height distributions for Copaifera regeneration were observed by Resende [12] and Rigamonti-Azevedo [46], unlike our results (Table 4). Resende et al [12] observed a change in distributional shape over a three year observation period, wherein the number of regenerating Copaifera in smaller diameter classes decreased, but increased in the largest diameter class.…”
Section: Effects Of Reduced-impact Logging On Diameter Distribution Ocontrasting
confidence: 99%
“…The shape of the diameter distribution of regeneration was not negative exponential (i.e., inverted J). Negative exponential diameter and height distributions for Copaifera regeneration were observed by Resende [12] and Rigamonti-Azevedo [46], unlike our results (Table 4). Resende et al [12] observed a change in distributional shape over a three year observation period, wherein the number of regenerating Copaifera in smaller diameter classes decreased, but increased in the largest diameter class.…”
Section: Effects Of Reduced-impact Logging On Diameter Distribution Ocontrasting
confidence: 99%
“…A maioria dos estudos baseia-se apenas em caracteres que permitem a identificação em nível de gênero e de morfotipos (Ferreira & Braz, 2001;Leite et al, 2001;Plowden, 2003;Rigamonte-Azevedo et al, 2006). Em pesquisas recentes, Medeiros & Vieira (2008) procederam, na Amazônia central, a identificação da espécie C. multijuga, para o morfotipo popularmente conhecido como copaíba mari-mari, assim como Alencar (1982).…”
Section: Introductionunclassified
“…In the state of Acre, Rigamonte-Azevedo (2006) found 29.4% of productive copaiba trees in a population of 273, and 40% in a population of 115 individuals, with an average yield of 2.92 liters per tree for both populations. In Amazonas State, Scudeller and Barbosa (2009) found 44% of productive individuals with a mean yield of 0.746 liters per tree.…”
Section: Environment Seedlingmentioning
confidence: 94%
“…Their fruit contains a ovoid seed surrounded by an aril. Flowering occurs between October and July and fruiting from June to October, with variations within these ranges depending on the region and climate, with no annual flourishing in some regions (VEIGA JR.;. In the region of Manaus, Amazonas, the flowering occurs from January to April and fruiting from March to August (BARBOSA et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation